Nieszczesny dar wolnosci - Tischner, Jozef (Krakow : Wydawn. Znak, 1993)
An essay on religious freedom and the relation of state and religion in post-communist Poland.
Keywords: Post-communism -- Poland; Religion and politics -- Poland; Liberty